3(7-x)=5x+37

Simple and best practice solution for 3(7-x)=5x+37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7-x)=5x+37 equation:


Simplifying
3(7 + -1x) = 5x + 37
(7 * 3 + -1x * 3) = 5x + 37
(21 + -3x) = 5x + 37

Reorder the terms:
21 + -3x = 37 + 5x

Solving
21 + -3x = 37 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
21 + -3x + -5x = 37 + 5x + -5x

Combine like terms: -3x + -5x = -8x
21 + -8x = 37 + 5x + -5x

Combine like terms: 5x + -5x = 0
21 + -8x = 37 + 0
21 + -8x = 37

Add '-21' to each side of the equation.
21 + -21 + -8x = 37 + -21

Combine like terms: 21 + -21 = 0
0 + -8x = 37 + -21
-8x = 37 + -21

Combine like terms: 37 + -21 = 16
-8x = 16

Divide each side by '-8'.
x = -2

Simplifying
x = -2

See similar equations:

| (7n-6)(7n-6)= | | 2x+6=26+12x | | -7x-4=37 | | 7x^2-x+10=0 | | 20.70*1150= | | y=25-2x^2 | | (6d-5)(4d-7)= | | 4a+6b=86 | | 32-6x=12-10x | | 5+x=3(x-7)+6 | | 5x+15y=55 | | (4x+1)(6x+3)= | | 5-2x=3+x-4-3x | | 2x+11=-5-2x | | 5q^2-2q=4q^2-4q+15 | | 3(p^2-18p+81)=81 | | -4(x+5)=10 | | 24+8=-2x+10x | | 4(x+7)=23 | | 3x+8-10x=14 | | M^2+8M=3 | | 1150/20.70%= | | 110/70= | | 35=3.50x+7 | | B^2=175 | | 172=12x-5+82 | | Y=3.50(4)+7 | | 8+3-12+6= | | Y=3.50(9)+9 | | 9x^2-12x=-1 | | 3.50x+7=9 | | 2+5n=27 |

Equations solver categories